AVICENNA'S CONTRIBUTION TO VASCULAR SURGERY - A.D. GAIBOV; O. NEMATZODA; E.L. KALMYKOV (Avicenna Tajik State Medical University, 2020)
The article reflects the main points of Avicenna's contribution to vascular surgery. The scientist in his work described a very detailed pathogenesis of bleeding, the formation of a false aneurysm, thrombus formation in the venous system, and also the principles of their treatment, which was subsequently widely recognized by modern scientists. His great creation - «The Canon of Medicine» - contributed to the worldwide recognition of Avicenna both in the East and in the West. The role of Avicenna is also great in the development of pharmaceutical science and pharmacology. In particular, his main scientific ideas are still used to create modern medicines based on natural herbs and substances.